Effect of the thickness of Sr2Bi4Ti5O18 transition layer on the properties of BiFeO3/Sr2Bi4Ti5O18 bilayer composite thin films. Issue 8 (1st June 2020) - Zhao, Xuefeng; Liu, HuiYing; Pan, Xiaoyue; Wang, LingXu; Feng, Zhe; Guo, Xiaodong; Shen, Peng; Ma, Zhibiao; Zhang, Fengqing; Tian, Qingbo; Fan, Suhua
Abstract: BiFeO3 (BFO)/Sr2 Bi4 Ti5 O18 (SBT) bilayer composite thin films were prepared using the sol-gel method. The influence of the SBT transition layer thickness on the properties of BFO/SBT bilayer composite thin films was studied. The results showed that an SBT transition layer with the proper thickness can improve the BFO/SBT bilayer composite film performance. X-ray diffraction (XRD) analysis revealed that a bismuth layered perovskite structure is formed in all of the thin films. The scanning electron microscopy (SEM) result showed that the BFO/80 nmSBT sample exhibits good crystallization, an improved density and a uniform minimum grain size compared with the other samples. The X-ray photoelectron spectroscopy (XPS) result showed that the Fe 2+ content and oxygen vacancy concentration are lowest in the BFO/80 nm SBT sample. This sample has good ferroelectric properties: the leakage current density has the lowest value of J = 5.21 × 10 -5 A/cm 2 among the samples at 350 kV/cm, 2Ec = 900 kV/cm, and 2Pr = 151 μC/cm 2 . At a low electric field (E<100 kV/cm), the leakage mechanism of the thin film is ohmic conduction, and the Fowler-Nordheim (F–N) tunneling effect is observed at a high electric field (E>100 kV/cm). The relative dielectric constant (εr) is 121, the dielectric loss (tanδ) is 0.024 at 10 5  Hz.